The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.19112/2413-6174-2020-21-2-13-22
|View full text |Cite
|
Sign up to set email alerts
|

Essential Trace and Ultra Trace Elements in Nutrition of Vegetarians and Vegans. Part 2. Iodine, Selenium, Chromium, Molybdenum, Cobalt

Abstract: In addition to the inhibitory effect of phytic and oxalic acids, other factors also affect the provision of vegans and vegetarians with essential elements. Selenium comes predominantly from plant products. However, its content in plants depends on the concentration in soils, which varies considerably in different regions. The source of iodine is seafood. Studies show that all food groups are at high risk of iodine deficiency, but vegans and vegetarians are at greater. In addition, remoteness from the seacoast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Считается, что патогенные микроорганизмы, как правило, более чувствительны к ионам данных элементов, чем непатогенные. Несмотря на то, что и серебро и золото обладают низким показателем всасывания в организме, они все еще остаются крайне перспективными элементами для внесения [8,9].…”
Section: Discussionunclassified
“…Считается, что патогенные микроорганизмы, как правило, более чувствительны к ионам данных элементов, чем непатогенные. Несмотря на то, что и серебро и золото обладают низким показателем всасывания в организме, они все еще остаются крайне перспективными элементами для внесения [8,9].…”
Section: Discussionunclassified
“…These vitamins and selenium levels intrinsically linked to a higher prevalence of dental caries. 15,17 Thus, a lack of nutrients may cause oral health issues such as the escalation of recurring aphthous ulcers and the emergence of glossodynia. 18 Too low B12 values can also lead to ulcers afferent to the oral cavity and glossitis, that is, an inflammation of the tongue, which leads to a change in its shape and color, generally leading it to swell and appear more red and sore, not to be confused with oral neoformations.…”
Section: Veganism and Increased Risk Of Periodontitismentioning
confidence: 99%
“…Also, in vegans, increased consumption of fruits and vegetables, which lowers salivary pH and causes erosive tooth surface loss, may hasten tooth surface loss. 17 The results of the meta-analysis conducted by Smits et al in 2020 suggested that vegans may be at a twice higher risk of tooth erosion as they consume more fruits and vegetables than other diets. 20,21 Dietary guidance is crucial to maintaining good oral health over the long run because vegan individuals are more susceptible to demineralization and acid erosion.…”
Section: Veganism and Erosionmentioning
confidence: 99%
“…Postoje određene grupe ljudi sa određenim potrebama u ishrani, na primer dijabetičari i gojazni pacijenti zahtevaju znatno veće količine hroma i vanadijuma 121,122 , a vegetarijanci i vegani imaju veću verovatnoću da imaju nedostatak ω-3 PUFAs 123 i joda 124 , 125 u odnosu na ljude na standardnom režimu ishrane. Međutim, nisu pronađeni značajni efekti ovih mikroelemenata na usnu duplju.…”
Section: Vegetarians and Vegansunclassified
“…There are certain groups of people with specific diet requirement. For instance, diabetic and obese patients require significantly higher amounts of chromium and vanadium 121,122 , and vegetarians and vegans are more likely to be deficient in ω-3 PUFAs 123 and iodine 124,125 than omnivores. However, the significant effects of these micronutrients on the oral cavity were not found.…”
Section: Vegetarians and Vegansmentioning
confidence: 99%